Patriarchy, gender, infantilisation: A cultural account of police intelligence work in Scotland. Issue 2 (June 2017) - Atkinson, Colin
Drawing upon qualitative research undertaken in Scotland, this paper provides new insights into police culture by exploring the interactions between sworn police officers and civilian intelligence analysts engaged in intelligence work. The claim is made that by exploring the cultural impact of intelligence analysis, it is possible to identify patriarchal dispositions within police culture and the emergence of a gender order in policing that subordinates femininity, youth and other masculinities that run counter to police culture's form of hegemonic masculinity. This gender order is interwoven with processes of infantilisation that inhibit the integration of intelligence analysts into police intelligence work. This article concludes by discussing the prospects for cultural change in policing from the inter-related perspectives of both social theory and professional practice.